MODEL SIMULATION OF DRY STORMWATER DETENTION POND WITH IPCC AR6 PROJECTED CLIMATE CHANGE SCENARIOS - Mah, Yau Seng; Hafiz Fadillah, Alhadi; Norazlina, Bateni; Fang Yenn, Teo (Faculty of Science and Technology, University of Biskra, 2024)
Dry detention ponds are good practices for stormwater management that control flow discharge by temporarily storing water and gradually releasing it with no permanent water ponding. A real-life dry stormwater detention pond in Sarawak, Malaysia, was selected for this study. The pond has a dimension of 80 (length) × 10 (top width) × 1.98 (depth) m3. The inlet is the end of a drain extended from a local government complex with a 27,800-m2 catchment area, and the outlet is an orifice with a 0.45-m diameter. The pond is characterized by a storage volume of 1,050 m3 based on a 30-min, 100-year average recurrent interval design storm. Another characteristic of the pond is the flow restriction imposed by the orifice outlet, in which water levels are always higher behind the orifice. The dry detention pond was tested against Intergovernmental Panel on Climate Change (IPCC) AR6 future scenarios by simulating catchments, adjacent drainage networks, and dry ponds with orifices using a stormwater management model. Maximum 1-day precipitation data were extracted from IPCC-WG1 Atlas according to AR6 future scenarios and periods. The data were normalized to 30-min rainfall temporal patterns. With the modelling, three hydraulic indicators were identified: water level, flow, and velocity. The high water level caused by the orifice outlet influenced the pond’s water levels. The expected rise of the pond’s water levels to the extent of overflowing was ruled out. Instead, water levels were maintained below the pond-full level due to the orifice. Besides, the ponding effect during the filling of the pond’s storage volume increased inflows from climate change-induced storms. The findings showed that the flow rates within the pond reduced gradually from the inlet to the outlet. Among the three indicators, only velocities along the length of the pond showed significant responses to AR6 future scenarios. The velocities increased in SSP2-4.5, SSP3-7.0, and SSP5-8.5, which calls for new solutions to the erosion of earthen pond walls.